Mucin-polysaccharide interactions: A rheological approach to evaluate the effect of pH on the mucoadhesive properties - de Oliveira Cardoso, Valéria Maria [UNESP] (2020)
The design of mucoadhesive drug delivery systems (DDS) based on polysaccharides at nanoscale or microscale is a relevant technological strategy for the mucosal delivery of several drugs. Findings about the potential mucoadhesive ability of these materials and the mechanisms that drive such interactions represents an important advance for the rational modulation of these properties, according to specific uses. The potential mucoadhesive abilities of gellan gum (GG) and retrograded starch (RS) were investigated at pH 1.2 and 6.8, which were considered biorrelevant for the gastrointestinal tract (GIT). The effects of these polysaccharides on the MUC rheology were also addressed. Rheological studies revealed high MUC-GG interactions at both pH values (1.2 and 6.8), expressing a high mucoadhesive ability, mainly in acidic media. MUC-GG interactions were driven, mainly, by hydrogen bonds. At an acidic pH, significant changes occurred in the MUC arrangements due to the strong MUC-GG interactions, as corroborated by scanning electron microscopy (SEM). The rheological behavior of MUC-RS indicated poor interactions between them and MUC arrangements were more preserved as evidenced by SEM. The results of this work indicated that the mixing of GG and RS can be a promising strategy to modulate mucoadhesiveness of DDS, according to specific therapeutic needs.